A study of segmentation of cannabis-oriented tourists from China based on motivation. Issue 1 (2nd January 2020) - Wen, Jun; Meng, Fang; Ying, Tianyu; Belhassen, Yaniv
ABSTRACT: In the wake of the early liberal policies of the Dutch government, coffee shops in Amsterdam have become famous for their outright sale and free use of cannabis-related products. Based on a sample of 654 Chinese tourists who consumed cannabis during their vacation in the city, this study proposes three clusters of cannabis tourists: cannabis enthusiasts, diversionists/recreationists, and the curious. Significant differences in sociodemographic characteristics and behavioural intentions were detected among these clusters. In light of the commercialization of cannabis in other destinations across the world, the research proceeded to discuss theoretical and practical implications for marketers and managers in the tourism industry.